Conspicuous consumption, social status and clubs - Fernando Jaramillo; Hubert Kempf; Fabien Moizeau (Fondazione Eni Enrico Mattei (FEEM), 2000)
The paper develops a signalling theory of conspicuous consumption where the drive toward spending on an otherwise unuseful good comes from the desire to enter clubs and benefit from the provision of club good financed by members of a club and from a social status effect. Individual incomes are unobserved and admission to a club is based on the inference of an individual's capacity to contribute to the public good. By entering in a club, individuals also gain a certain social status. This inference in turn is based on the signal emitted by spending on a conspicuous good. Because of the joint incentives of club good and social status, people may be induced to overspend in the conspicuous good. We characterise both the pooling equilibria and the separating equilibria of the signalling game played by individuals. We then ask whether taxation can be Pareto-improving and which tax scheme would be chosen by the median voter in this society
Keywords: 330; Clubtheorie; Lokale öffentliche Güter; Signalling; Asymmetrische Information; Sozialer Status; Steuer; Theorie